Working conditions in COVID-19 hospital units: perceptions of nursing workers - Alexa Pupiara Flores Coelho Centenaro; Andressa de Andrade; Gianfábio Pimentel Franco; Lílian Moura de Lima Spagnolo; Leticia Silveira Cardoso; Marta Cocco da Costa; Clarice Alves Bonow; Rosângela Marion da Silva (Universidade Federal do Rio Grande do Sul, 2023)
ABSTRACT Objective: To know the perceptions of nursing workers about their working conditions in COVID-19 hospital units. Method: Qualitative, descriptive, multicenter study, carried out in September 2020 and July 2021 with 35 nursing workers from COVID-19 units of seven hospitals in Rio Grande do Sul, Brazil. Data were produced through semi-structured interviews and submitted to thematic content analysis with the support of NVivo software. Results: The participants reported availability of material resources and personal protective equipment, but perceived a lack of human resources, multiprofessional support and extra absorption of tasks, resulting in the intensification of work and culminating in overload. Professional and institutional aspects were also mentioned, such as fragility in professional autonomy, wage lag, payment delays and little institutional appreciation. Conclusion: Nursing workers in the COVID-19 units lived with precarious working conditions, worsened by organizational, professional and financial elements.